Business Management Training and Assistance Towards Bankable MSMEs in Malaysia - Indanazulfa Qurrota A'yun; Mufti Alam Adha; Indah Shofiyah (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Micro, Small and Medium Enterprises (MSMEs) play an important role in a country's economy. MSMEs are the most strategic economic sector and concern the livelihoods of many people so they can become the backbone of the country's economy. Despite having an important role in the economy, many MSMEs in Malaysia still face challenges in improving their business management capabilities and meeting the requirements as MSMEs that meet the standards for obtaining funding from banks. One of the efforts made to help MSMEs in Malaysia is by holding a Business Management Training and Assistance program towards Bankable MSMEs. This program is designed to help MSMEs improve their skills and knowledge in managing their business more effectively and efficiently, as well as fulfill the requirements as bankable MSMEs so they can access financing sources more easily. Apart from that, the important role of technology in increasing business scale is also the main thing in this training. Business and financial governance is also an important part in raising the level of MSME business. By maximizing the function of technology and increasing capacity in business governance, MSMEs can reach a wider range of consumers and provide maximum service to their customers. In this way, MSMEs in Malaysia can grow to a larger scale. This international service activity was carried out on 23-24 July 2023 in Johor Bahru, Malaysia. During this offline implementation, the service team held training and handed over meat grinding equipment.